2019
DOI: 10.1002/biof.1535
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen, nitrogen, and sulfur species in human male fertility. A crossroad of cellular signaling and pathology

Abstract: Infertility is a significant global health problem that currently affects one of six couples in reproductive age. The quality of male reproductive cells dramatically decreased over the last years and almost every aspect of modern life additionally worsen sperm functional parameters that consequently markedly increase male infertility. This clearly points out the importance of finding a new approach to treat male infertility. Redox signaling mediated by reactive oxygen, nitrogen and sulfur species (ROS, RNS, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 139 publications
0
19
0
Order By: Relevance
“…Indeed, when superoxide anion generation exceeds the limited antioxidant capacity of the sperm cell, it has the ability to propagate the formation of non-radicals, including hydrogen peroxide (H 2 O 2 ), and in the presence of Fe 3+ , the formation of alternative radicals such the hydroxyl anion (OH − ) via Haber-Weiss and Fenton reactions [26]. Additional ROS containing nitrogen atoms (such as NO, NO 3 − , NO − , N 2 O, and HNO 3 ) are also able to be formed [27,28] and collectively, these powerful oxidants have the potential to trigger the peroxidation of membrane lipids and a concomitant loss of sperm function [29]. In studies conducted in rats it has been shown that the presence of dead spermatozoa can also promote higher than normal levels of H 2 O 2 [30].…”
Section: Spermatozoamentioning
confidence: 99%
“…Indeed, when superoxide anion generation exceeds the limited antioxidant capacity of the sperm cell, it has the ability to propagate the formation of non-radicals, including hydrogen peroxide (H 2 O 2 ), and in the presence of Fe 3+ , the formation of alternative radicals such the hydroxyl anion (OH − ) via Haber-Weiss and Fenton reactions [26]. Additional ROS containing nitrogen atoms (such as NO, NO 3 − , NO − , N 2 O, and HNO 3 ) are also able to be formed [27,28] and collectively, these powerful oxidants have the potential to trigger the peroxidation of membrane lipids and a concomitant loss of sperm function [29]. In studies conducted in rats it has been shown that the presence of dead spermatozoa can also promote higher than normal levels of H 2 O 2 [30].…”
Section: Spermatozoamentioning
confidence: 99%
“…Substantial information is available regarding the role of NO in crucial sperm processes prior to fertilization, such as capacitation, hyperactivation, acrosome reaction, and zona pellucida binding [19,[40][41][42]. Furthermore, the role of NO has been widely investigated during semen handling and storage [43,44].…”
Section: Mechanisms Of Action Of No In Spermatozoamentioning
confidence: 99%
“…A third mechanism of action occurs at high concentrations of NO, which directly provokes a post-translational modification of proteins, reversibly by S-nitrosylation or irreversibly by tyrosine nitration [40]. Within the human spermatozoa, more than 200 proteins have been identified that are modified by NO via the process of S-nitrosylation [58], which is the covalent union of NO and sulfur of cysteine, forming a nitrosothiol group (-SNO) within the molecule.…”
Section: Mechanisms Of Action Of No In Spermatozoamentioning
confidence: 99%
See 2 more Smart Citations